A survey on the preferred learning styles among form four students / Mohd Haizam Hashim - Hashim, Mohd Haizam (2011)
Research has shown learning styles to be one of the factors that influences students’ motivation to learn a language. As such, this study attempts to replicate a study by Reid (1987) to identify the learning style preferences of students. This was accomplished by administering Reid’s (1987) Perceptual Learning Style Preference questionnaire (PLSP) to 104 students of SMK Padang Temu, in Melaka. The results of this study show that there are differences in learning styles according to gender and grade achieved. This study also shows that there is a difference between the group learning style and grades received in a standardized test. The study has concluded that there is a connection between learning styles, gender and grades.